HUBUNGAN PENGETAHUAN PENGGUNAAN APD, PERILAKU PENGGUNAAN APD, DAN ERGONOMI DENGAN KEJADIAN KECELAKAAN KERJA PADA PEKERJA DI PABRIK KELAPA SAWIT DI ROKAN HULU RIAU - Irham Ansya Bastian; Santoso Santoso; M. Kamali Zaman (Universitas Lancang Kuning, 2023)
The number of work accidents has increased by around 5-10% annually, the main causes of work accidents are still the same due to low awareness of the importance of implementing Occupational Health and Safety (OSH) among industry and society. This study used a cross sectional study conducted at PT. Gunung Sawit Mas (GSM), North Tambusai, Rokan Hulu, Riau. By collecting data using a questionnaire and the Ovako Working Analysis System (OWAS) method. The results of this study found that there was a significant relationship between knowledge of using (Personal Protective Equipment) PPE and the incidence of work accidents among workers at the PT. Gunung Sawit Mas Rokan Hulu. There is a significant relationship between the behavior of using PPE and the incidence of work accidents among workers at the PT. Gunung Sawit Mas Rokan Hulu. Workers who do not fully use PPE are 3.9 times more at risk of experiencing work accidents compared to workers who use PPE completely. There is a significant relationship between ergonomics and the incidence of work accidents among workers at the PT. Gunung Sawit Mas Rokan Hulu. Workers who are not ergonomic are 7.8 times more at risk of having work accidents compared to workers who are ergonomic